Application of chemometric combination NIRS technology for analysis of mixed coconut oil levels in Aceh Patchouli Oil. Issue 1 (1st December 2022) - Munandar, Aris; Mulyati, Sri; Hasanuddin,; Zulfahrizal,
Abstract: Patchouli oil could be a sort of fundamental oil that's delivered from the refining of the leaves, twigs, and stems of the patchouli plant. One of the problems that occur in determining the quality of patchouli oil is mixing with other oils, such as coconut oil, causing the quality of patchouli oil to be low and the selling price to be cheap. The reason of this inquire about is to construct a show for evaluating the levels of coconut oil mixed in Aceh patchouli oil using the chemometric method. This research uses patchouli oil (crude oil) and coconut oil. The NIRS tool used for spectrum acquisition is the FT-IR IPTEK T-1516. NIRS technology is combined with chemometric methods with two multivariate analyses, namely the PCR and PLS models. The comes about appeared that the PLS calibration show was superior than the PCR calibration model. The RPD value in the non pretreatment PLS calibration model was 3.96 and increased with the presence of SNV pretreatment to 4.78 so that it was included in the category of very good prediction model accuracy. While the PCR calibration model included in the prediction category is still rough, both non-pretreatment and with SNV pretreatment, which are 1.45 and 1.50, respectively.